Pengaruh BOPO, LDR, NPL Terhadap ROA Perusahaan Perbankan Yang Terdaftar di BEI - Mesrawati Mesrawati; Vieri Suryana Purba; Ade Safitri Purba (Akuntansi & Ekonomika, 2019)
The objective of the research was to analyze the influence of BOPO, LDR and NPL to Return on Asset (ROA) listed on BEI period 2014-2017 . The sampling method that used in this research is Purposive Sampling by the use of consideration and certain cretaria,obtained a sample of 31 companies. The date were analyzed by using multiple linear regression analysis method.The result of the research that simultaneosly bopo,ldr,npl,had significant effect to return on asset ,but partially, operational cost to operational expenses ,non performing loan negative significant effect to return on assett and loan deposit ratio not significant effect to return on asset.